Research of Gear Modeling with Considering Hob Installation Error - Wu Pingan; Wang Tie; Zhang Ruiliang; Wu Zhifei; Liu Yaqiong (Jixie chuandong, 2016)
With the development of gear application technology,the higher requirements on gear precision are put forward,in order to achieve goals of high speed,high power,low noise and high transmission accuracy in gear transmission. In the gear hobbing process,if the tool geometry errors is ignored,the hob installation errors have become a major factor affecting the gear smooth precision. It starts from hob installation errors,the influence of hob installation errors on gear precision is analyzed. According to the principle of gear generating machining,the gear coordinate system and tool coordinate system are established,then by using the method of coordinate transformation,the gear tooth profile equation is deduced,which provides the design basis for 3D parametric gear precise modeling.